In Vivo Detection and Quantification of Tetracycline by Use of a Whole-Cell Biosensor in the Rat Intestine - Bahl, Martin Iain (American Society for Microbiology, 2004)
An Escherichia coli biosensor strain, harboring the plasmid pTGFP2, was introduced into the gastrointestinal tract of gnotobiotic rats that continuously received drinking water containing tetracycline. Plasmid pTGFP2 contains a transcriptional fusion between a green fluorescent protein (GFP) gene and a tetracycline-regulated promoter and was shown to produce a proportional GFP signal in response to exposure to various tetracycline concentrations when harbored by an E. coli strain. The plasmid was highly unstable in the host bacteria colonizing the intestinal system of the animals, and rapid plasmid loss was observed. Reintroduction of the E. coli MC4100/pTGFP2 strain into animals already colonized by the plasmid-free E. coli strain the day before euthanasia made it possible to extract and analyze the biosensors from intestinal samples. The induction of GFP in the biosensor cells extracted from the animals was estimated on a single-cell basis by use of flow cytometry, and the mean induction of GFP in the samples was compared to a standard curve prepared from known tetracycline concentrations. The results showed that the bioavailable tetracycline concentration within the bacterial growth habitat of the intestine was proportional to the concentration of tetracycline in drinking water but represented only approximately 0.4% of the intake concentration. This is a significant finding which will help to clarify antimicrobial therapy in the intestinal environment.